Morays need to get a grip!—The California moray (Gymnothorax mordax) uses its body and the environment for leverage during feeding - Maya M. McElfish; Avery A. McDaniel; Sacha E. O’Connor; August D. Robinette; Rita S. Mehta (Environmental Biology of Fishes, 2026)
Many predatory fishes hunt and feed in structurally complex environments making their feeding behaviors challenging to observe. We designed a transparent microhabitat to document how the California moray ( Gymnothorax mordax ) uses its elongated body to apply leverage during crevice foraging within the rocky reef. To generate leverage, these predatory fish use complex behaviors to extract prey from tight spaces. Morays form anchors by using the body in combination with the surrounding environment to maintain position. We demonstrate that morays can brace themselves internally within the crevice by strategically pushing against the interior surfaces, forming sinusoidal waves with their body, creating one to four bracing anchor points. More often, morays anchor themselves by extending their tail out of the crevice and wrapping around the crevice edge to facilitate pulling. In addition, we observed morays using leverage through knot tying, using three distinct patterns of knots with the simple overhand knot observed most frequently, which can occur within and outside of crevices. Our observations highlight the tactical behavioral diversity these cryptic predators use to overcome physical constraints and forage successfully in spatially complex environments.